Ink Engineering of Transport Layers for 9.5% Efficient All‐Printed Semitransparent Nonfullerene Solar Cells. (26th November 2020) - Corzo, Daniel; Bihar, Eloïse; Alexandre, Emily Bezerra; Rosas‐Villalva, Diego; Baran, Derya
Abstract: New polymer donors and nonfullerene acceptors have elevated the performance and stability of solar cells to higher grounds. To achieve their full potential, they require their adaptation to scalable and cost‐effective solution manufacturing techniques for large area deposition. Likewise, formulating scalable solution‐based transport layer inks that are compatible with the photoactive layer is imperative. This manuscript reports the full integration of solution‐based transport layers and electrode alongside a PTB7‐Th:IEICO‐4F bulk heterojunction in inverted architecture through inkjet‐printing, resulting in power conversion efficiencies up to 12.4% opaque devices and 9.5% semitransparent devices with average visible transmittance values of 50.1%, including hole transport layer. The wetting envelope of the highly‐hydrophobic photoactive layer alongside the surface energy of candidate solutions and solvents allows the formulation of thick transport layer inks that are compatible with the drop‐on‐demand inkjet‐printing process and yield uniform and homogenous films. Moreover, the surface energy components of the donor and acceptor serves as a fingerprint to assess the vertical stratification of the photoactive layer with the inclusion of different solvents. This methodology addresses a scale‐up bottleneck of solution‐based transport layers for high‐efficiency organic cells, enabling its adaptation to high‐throughput techniques including slot‐die and roll‐to‐roll coating. Abstract : 9.5% semitransparent solar cells with ultrahigh transmission in the visible range (50% AVT) are fabricated via inkjet printing. The effect of different photoactive layer ink solvents on the vertical stratification and performance is explored. The formulation of transport layer inks compatible with highly hydrophobic active layers and with scalable printing processes permits the use of a semitransparent electrode grid.